Analisis Komparasi Personal Selling, Advertising Terhadap Keputusan Pembeli Produk Rokok Djarum Dan Rokok Gudang Garam Di Surabaya - Rusdiana, Novita; Andayani, Sri; Maduwinarti, Ayun (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTThis study aims to determine whether there are differences between personal selling and advertising variables on the purchasing decisions of Djarum and Gudang Garam cigarette products in Surabaya. This study uses quantitative methods with sampling aimed at consumers who have made a decision to purchase Djarum and Gudang Garam cigarettes, the number of samples is 100 respondents who are divided into two, 50 from Djarum respondents and 50 from Gudang Garam respondents, data collection using online questionnaires or google forms. And testing tools were carried out in the form of Validity Test and Reliability Test, as well as data analysis techniques with Variance Test and Independent Sample t-Test. The results obtained from this study indicate that: 1. There is a significant difference in the personal selling variable on Djarum and Gudang Garam cigarettes with a significant personal selling result with a probability value (Sig-t) of 0.000 <0.05 which is accepted. 2. There is a significant difference in the advertising variable on Djarum and Gudang Garam cigarettes with a significant advertising result with a probability value (Sig-t) of 0.002 <0.05 which is accepted. 3. There is a significant difference between the Djarum and Gudang Garam cigarette purchase decision variables with a significant probability of purchasing decisions with a probability value (Sig-t) of 0.001 <0.05 which is accepted.Keywords: cigarettes, differences, personal selling, advertising, buying decisions